A Low-Cost VR Imersive Learning Tool for MicroBiology - Fernandes, Larissa; da Silva, Armando Paulo; da Silva, Mateus Calzavara; Damasceno, Eduardo Filgueiras (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2021)
Educators often struggle to teach cellular and molecular processes in microbiology because they usually only have tools based on only two dimensions and are not as attractive as multimedia tools. Learning research has demonstrated that visualizing processes in three dimensions aids learning, and animations are effective visualization tools for novice learners and aid with long-term memory retention. Thus, with increasing adoption of immersive virtual reality as an enabling strategy for teaching has challenged researchers, educators, and enthusiasts to produce both tools and content for these tools. High-fidelity graphics and immersive content using projection on increasingly inexpensive glasses have allowed students to explore complex subjects in a way that traditional teaching methods cannot. In this way, this work presents a prototype of a tool to facilitate the teaching of microbiology, contemplating both the pedagogical requirements of educational software and the technological ones necessary in the construction of an immersive virtual reality environment. Added to this proposal is the requirement to present a low-cost tool for both editing and visualization.